Tracked Changes. Fine ceramics (advanced ceramics, advanced technical ceramics). Test method for self-cleaning performance of semiconducting photocatalytic materials under indoor lighting environment. Measurement of water contact angle. (1st August 2023) - British Standards Institution,
No abstract available